2015
DOI: 10.3389/fgene.2015.00167
|View full text |Cite
|
Sign up to set email alerts
|

An interpretive review of selective sweep studies in Bos taurus cattle populations: identification of unique and shared selection signals across breeds

Abstract: This review compiles the results of 21 genomic studies of European Bos taurus breeds and thus provides a general picture of the selection signatures in taurine cattle identified by genome-wide selection-mapping scans. By performing a comprehensive summary of the results reported in the literature, we compiled a list of 1049 selection sweeps described across 37 cattle breeds (17 beef breeds, 14 dairy breeds, and 6 dual-purpose breeds), and four different beef-vs.-dairy comparisons, which we subsequently grouped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 152 publications
(213 reference statements)
2
111
0
2
Order By: Relevance
“…These regions included well-known genes that were previously reported as potential candidates of selection signatures in cattle [38], such as MTSN ( myostatin ) on BTA2, suggested in several beef cattle populations [3941], KIT - LG ( kit - ligand ) on BTA5 with a very large peak in the BP population, MC1R ( melanocortin 1 receptor ) on BTA18, which controls the production of eumelanin (black) or pheomelanin (red) pigments [42] and appears to be relevant in populations with black (AV and Mo) or red (Re) coat color. Moreover, it should be also highlighted that the region on BTA6 that includes LAP3 ( leucine aminopeptidase3 ), LCORL ( ligand dependent nuclear receptor corepressor - like ) and NCAPG ( non - SMC condensing I complex, subunit G ) and was identified in two meta-analyses [38, 43] as one the genomic regions that is most frequently identified with signatures of selection in the bovine genome. The genomic region identified on BTA7 includes the CAMLG ( calcium modulating ligand ) and TCF ( transcription factor 7 ) genes, which are close to a strong signature of selection that was reported by Gautier [44] and is associated with the VDAC1 ( voltage - dependent anion - selective channel protein 1 ) gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These regions included well-known genes that were previously reported as potential candidates of selection signatures in cattle [38], such as MTSN ( myostatin ) on BTA2, suggested in several beef cattle populations [3941], KIT - LG ( kit - ligand ) on BTA5 with a very large peak in the BP population, MC1R ( melanocortin 1 receptor ) on BTA18, which controls the production of eumelanin (black) or pheomelanin (red) pigments [42] and appears to be relevant in populations with black (AV and Mo) or red (Re) coat color. Moreover, it should be also highlighted that the region on BTA6 that includes LAP3 ( leucine aminopeptidase3 ), LCORL ( ligand dependent nuclear receptor corepressor - like ) and NCAPG ( non - SMC condensing I complex, subunit G ) and was identified in two meta-analyses [38, 43] as one the genomic regions that is most frequently identified with signatures of selection in the bovine genome. The genomic region identified on BTA7 includes the CAMLG ( calcium modulating ligand ) and TCF ( transcription factor 7 ) genes, which are close to a strong signature of selection that was reported by Gautier [44] and is associated with the VDAC1 ( voltage - dependent anion - selective channel protein 1 ) gene.…”
Section: Resultsmentioning
confidence: 99%
“…3) confirmed some of the signals of selection that were detected in the first axis, but also revealed several new ones that are shared by several populations and located on five chromosomes: BTA2 (between 61,684,232 and 62,199,344 and between 72,158,144 and 73,356,296 bp), BTA7 (between 20,612,988 and 21,163,812 bp), BTA13 (between 11,860,881 and 12,062,522 bp), BTA16 (between 44,612,592 and 45,846,144 bp) and BTA21 (between 32,207,264 and 32,414,316 bp). Previously, two meta-analyses [38, 43] showed that these regions were also associated with signatures of selection in other populations. Among the genes included in these regions, some of them may be good candidates for being affected by selection i.e.…”
Section: Resultsmentioning
confidence: 99%
“…These signatures must be related to favorable alleles that either started to increase in frequency before the divergence of the breeds or were selected in parallel in different breeds. However, selection signatures that are specific to one breed are interesting because they illustrate the importance of this breed for cattle functional diversity (Gutierrez-Gil et al 2015). We therefore derived a way of finding clear breedspecific sweeps as follows.…”
Section: Analysis Of Neutral Samplesmentioning
confidence: 99%
“…The SERPIND1 gene in mammals plays a crucial role in the control of the endopeptidases that mediate important pathways, such as blood coagulation, fibrinolysis, inflammation and complement activation (Rau et al 2007;Silverman et al 2001), some of which are considered the host's first line of defence to hematophagous and blood-dwelling parasites. The POU1F1 gene encodes a protein reportedly involved in productive life (Huang et al 2008), whereas PTK2 , FOXF2 (Capomaccio et al 2015) and LAMB3 (Gutiérrez-Gil et al 2015) reportedly encode proteins associated with milk production traits. ZBTB20 is a gene that overlaps the bovine QTL regions associated with milk traits and encodes a transcription factor that has been implicated in hematopoiesis, oncogenesis and the immune response in mammals (dos Santos et al 2017).…”
Section: Cnvr Gene Contents and Functional Annotationsmentioning
confidence: 99%